PENGARUH BEBAN KERJA, KEPUASAN KERJA, KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION GEN-Z TANGERANG SELATAN - Azhara zahra Rachamani; Maswanto Maswanto (Taksasila Edukasi Insani, 2026)
Businesses are facing a serious problem as a result of the high intention of turnover among Generation Z workers, especially in cities like South Tangerang City. The purpose of this study is to examine how Generation Z employees' intentions to leave a company are impacted by their workload, job satisfaction, and organizational commitment. This study uses a survey method in a quantitative manner. Fifty members of Generation Z who currently work or have previously worked in South Tangerang City were given questionnaires using a Likert scale to complete in order to gather data. Multiple linear regression analysis, validity testing, reliability testing, and classical assumption testing are some of the data analysis methods. The findings show that organizational commitment, workload, and job satisfaction all significantly and partially influence turnover intention. Workload has the greatest correlation with turnover intention among the independent factors. These results emphasize how crucial it is to control workload proportionately, improve job happiness, and increase organizational commitment as tactical measures to lower the intention of Generation Z workers to leave their jobs.Keywords workload, job satisfaction, organizational commitment, turnover intention, Generation Z